“Nós comemos e regurgitamos”: feminismos transnacionais e coalizões potenciais a partir da marcha das vadias de Goiânia/GO - Batista, Paula Nogueira Pires (2017)
This work aims to think about the potentialities of transnational feminist political coalitions based on ethnographic experience that focused on Slutwalk of the city of Goiânia / GO ("Marcha das Vadias" - MdV / GO) in the years 2014, 2015 and 2016. For this, I interpret that this March would be a contemporary "young" feminist expression. The analysis proposes intersectionality, taking into account the different social markers of difference that have emerged in the field, such as gender, "race" / color, class, sexuality and age / "generation". Thus, three major axes of analysis are thought: 1) Transnational flows of feminisms; 2) Intersectionality and ethnic-racial issues; 3) Generational differences and different feminisms in play. As an analytical possibility, I propose the idea of ​​intersectional feminist whiteness, thought from the racialization of white social experience on the March.